2022
DOI: 10.3389/fendo.2022.815960
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dyslipidemia incidence in Chinese early-stage breast cancer patients following different endocrine therapies: A population-based cohort study

Abstract: BackgroundThere is lack of large-scale real-world research evidence showing the impact of endocrine therapy on blood lipids in Chinese breast cancer patients, especially those with premenopausal breast cancer. Based on a large breast cancer cohort at West China Hospital, we aimed to compare the risk of dyslipidemia between premenopausal and postmenopausal women based on the endocrine therapy used.MethodsA total of 1,883 early-stage breast cancer (EBC) patients who received endocrine monotherapy [selective estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In contrast, prior research frequently reports no signi cant changes in lipid pro les with AI use [19,34,35,41,43,44]. Furthermore, studies investigating dyslipidemia as an outcome endpoint reported no association in BC survivors comparing AI to tamoxifen users [40,43]. Since tamoxifen use is associated with improvements in lipid biomarkers, its cardioprotective effects may mask any possible deleterious impacts of AI use when compared with each other.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, prior research frequently reports no signi cant changes in lipid pro les with AI use [19,34,35,41,43,44]. Furthermore, studies investigating dyslipidemia as an outcome endpoint reported no association in BC survivors comparing AI to tamoxifen users [40,43]. Since tamoxifen use is associated with improvements in lipid biomarkers, its cardioprotective effects may mask any possible deleterious impacts of AI use when compared with each other.…”
Section: Discussionmentioning
confidence: 93%
“…Our nding of no association with dyslipidemia in pre-and postmenopausal tamoxifen users is generally consistent with the existing literature. Studies suggest favorable lipid pro les, including decreased total cholesterol and low-density lipoprotein cholesterol and increased high-density lipoprotein cholesterol, for tamoxifen users in both premenopausal and postmenopausal BC survivors [31][32][33][34][35][36][37][38][39][40][41][42]. In contrast, prior research frequently reports no signi cant changes in lipid pro les with AI use [19,34,35,41,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…A 100-month follow-up of the ATAC trial revealed a higher incidence of hypercholesterolemia in the ANA group compared to the TAM group among postmenopausal BC patients [ 20 ]. A large cohort study also found that, whether postmenopausal or premenopausal, TC and LDL-C levels in the AI group were higher than in the SERM group [ 21 ]. This difference may be due to the different mechanisms between AIs and SERMs.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that using OFS at a younger age may exacerbate lipid-related events in premenopausal patients [ 26 ]. However, a 5-year cohort study revealed a higher incidence of dyslipidemia in postmenopausal patients compared to their premenopausal counterparts (42.6% vs. 32.6%) [ 21 ]. This study also showed a higher incidence of dyslipidemia in postmenopausal patients, especially in the first year after medication, then the difference disappeared.…”
Section: Discussionmentioning
confidence: 99%